Does the efficiency of a counter-herding device depend on seabed contact? - Melli, Valentina; Krag, Ludvig Ahm; Herrmann, Bent; Karlsen, Junita Diana; Feekings, Jordan (Fisheries Research, 2020)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. To prevent unwanted fish bycatch from entering the trawl, we modified a counter-herding device, FLEXSELECT, developed for a Northeast Atlantic Nephrops ( Nephrops norvegicus ) trawl fishery. FLEXSELECT, which was designed to direct fish away from the trawl by means of sweeping ropes in the herding area, has been shown to be highly effective on both roundfish and flatfish species. However, by adding sweeping elements we could be increasing the benthic impact of trawling. Therefore, in this study we investigated if the effect of FLEXSELECT can be maintained when raising the ropes off the seabed. A reduction in fish bycatch could still be achieved, but the effect of FLEXSELECT raised with respect to the previous design was significantly different for four of the seven species analysed. While for some species the effect was lower, it substantially increased for cod ( Gadus morhua ), making it highly relevant for the Nephrops fisheries, as well as for other fisheries in needs of avoiding cod catches. The results offer insights regarding species behavioural responses to FLEXSELECT raised , to be used for future developments of counter-herding devices in commercial fisheries without the addition of seabed impact to the baseline gears.